Preparation and Evaluation of Herbal Gel Containing Multiple Plant Extracts for Acne Treatment - Versha Sharma; Poonam Kumari; Kavita Kashyap (International Journal of Biochemistry and Biomolecule Research, 2025)
A persistent inflammatory condition affecting the pilosebaceous unit, acne is caused by an increase in sebum production by sebaceous glands and an incorrect desquamation of hair follicles in response to rising testosterone levels throughout teenage years. Follicular obstruction results in follicular distention, which frequently triggers an inflammatory reaction and the growth of the Propionibacterium acnes bacteria. This project mainly focused on the formulation of a herbal gels for acne. These days, herbal gels are widely used because they're considered safe and free from side effects. The market for herbal drugs id growing day by day. This study focuses on creating and assessing a new poly-herbal anti acne formulation that includes neem leaf (Azadirachta indica) hydro-alcoholic extract, turmeric powder extract, and aloe vera extract. We suggest using neem (Azadirachta indica) leaf hydroalcoholic extract, Curcuma longa powder extract, and aloe vera extract, despite the fact that there are many anti-acne herbal formulations on the market. In this literature many strong properties of plants like antibacterial, antioxidant, and anti-inflammatory have been documented. The gelling ingredient carbopol 940 was used in different concentrations to prepare different formulation batches. Prepared formulas were assessed. The marketed preparation and the optimized formulation were evaluated. The attempt to create a herbal gel from neem leaf (Azadirachta indica) hydro-alcoholic extract, turmeric powder, and aloe vera extract is excellent. The gels had anti-acne properties and were non-irritating, according to the results. When tested against a standard, the efficacy was nearly identical to that of the polyherbal gel. concluded that the extract from this study demonstrated stability and was thought to be a useful herbal remedy for treating acne.
Keywords: Aloe vera extract; Poly-Herbal Anti-Acne Formulation; gel; neem (Azadirachta indica); turmeric powder (Curcuma longa)